Influence of Project-Based Learning Model that Aided Matrix Laboratory toward Creative Thinking Skills Viewed from College Student's Science Generic Skills - Muhammad Nasir (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This study aimed at anlyzing the influence of project-based learning that aided matrix laboratory toward college student’s creative thinking skills and the influence of science generic skills toward the relationship between project -based learning model that aided matrix laboratory and college student’s creative thinking skills. The method used in this research was pre-experiment method with design is one shot case study. Data analyzed by regression test with moderating variable. The Results of the analysis found that (1) there is the influence of project based learning model that aided matrix laboratory toward college student's creative thinking skills (44.3%); (2) there is the influence of science generic skills to the relationship between project-based learning model that aided matrix laboratory and college student’s creative thinking skills (28.6%). The science generic skills had been contributed to strengthen the relationship between project-based learning model that aided matrix laboratory and college students’s creative thinking skills. Keywords: college students’s creative thinking skills, matrix laboratory, project-based learning model